Analysis of Use of Antisense Oligonucleotides for Prevention and Treatment of Hazardous and Extremely Hazardous Viral Infectious Diseases - A. A. Petrov; V. N. Lebedev; T. E. Sizikova; T. M. Plekhanova; S. V. Borisevich (Антибиотики и Химиотерапия, 2020)
The article describes different generations of antisense oligonucleotids (unmodified oligonucleotids, phosphorothioate oligomers, 2’-0-methyl and 2’-0-methoxy-ethyl modification of oligomers, phosphordiamidate morpholine oligomers and small interfering RNAs), the possible mechanism of their action, their use for prevention and treatment of hazardous and extremely hazardous viral infectious diseases. Phosphordiamidate morpholine oligomers and small interfering RNAs are most widely used in the development of emergency prevention and treatment of hazardous and extremely hazardous viral infectious diseases. The authors conclude, that further improvement of medications based on antisense oligonucleotids may be achieved by improving the structure of the latter and carrying out the search for new chemical modifications.